The Art of the Exploit: Gender Hacking and Political Agency. - Hester, Helen (Paragraph, 2023)
This article considers the idea of gender hacking, particularly as it circulates in Paul B. Preciado's Testo Junkie, and places this in the context of wider discourses of both bio- and computer hacking. Of particular interest is how a hacking paradigm has come to inform twenty-first-century theories of activist intervention, and the implications of this for contemporary conceptions of political agency. Drawing out the parallels between conceptualizations of hacking and transgression, the article considers both the possibilities and the potential limitations of thinking about sociopolitical changemaking in these terms. Ultimately, it uses theories of transgression to propose a rethinking of the distinction between engineering and hacking, with a view to negotiating the conflict between micropolitical hormonal intervention and ambitions toward re-engineering biotechnical hegemony in gender-hacking projects.